2015
DOI: 10.1186/s12958-015-0023-2
|View full text |Cite
|
Sign up to set email alerts
|

A possible role for AMP-activated protein kinase activated by metformin and AICAR in human granulosa cells

Abstract: BackgroundWomen with polycystic ovary syndrome (PCOS) are generally insulin- resistant and are consequently often treated with metformin. We investigated the effect of metformin and AICAR on the AMP-activated protein kinase (AMPK) pathway.MethodsWe evaluated the effects of 5-amino-imidazole-4-carboxyamide-1- beta-D-ribofuranoside (AICAR) and metformin on tumor necrosis factor (TNF)-alpha- stimulated chemokine production in human granulosa cells. The phosphorylations of AMPK, I-kappaB, 4E-BP-1, p70S6K were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…Moreover, AMPK was shown to reduce the activity of NF-κB and the levels of the pro-inflammatory cytokine TNFα [25]. Metformin, the agonist of AMPK, could attenuate TNFα-and chemokinemediated inflammatory responses and granulocyte dysfunction in an AMPK-dependent manner [26]. Previous studies have suggested that BAL could upregulate AMPK [27] and thus we verified whether activation of AMPK participated in the effects of BAL on PCOS.…”
Section: Discussionmentioning
confidence: 63%
“…Moreover, AMPK was shown to reduce the activity of NF-κB and the levels of the pro-inflammatory cytokine TNFα [25]. Metformin, the agonist of AMPK, could attenuate TNFα-and chemokinemediated inflammatory responses and granulocyte dysfunction in an AMPK-dependent manner [26]. Previous studies have suggested that BAL could upregulate AMPK [27] and thus we verified whether activation of AMPK participated in the effects of BAL on PCOS.…”
Section: Discussionmentioning
confidence: 63%
“…As a result, the ability of MF to improve energy metabolism, prevent lipotoxicity and restore the redox balance in the ovaries is another mechanism of its beneficial effect on folliculogenesis and the ovulatory cycle in PCOS. In human granulosa cells, through AMPK-dependent mechanisms, MF suppresses the tumor necrosis factor-α (TNF-α)-induced production of pro-inflammatory cytokines, interleukin-8 and chemokine CXCL1/GROα [ 303 ]. The other AMPK activators, such as AICAR and Baicalin, also reduce TNF-α- and chemokine-mediated inflammatory responses in ovarian cells [ 303 , 304 ].…”
Section: Metformin and Polycystic Ovary Syndromementioning
confidence: 99%
“…15,59 Tosca et al showed that AMPK activation through Aicar could decrease the abundance of HSD3B, CYP11A1, and STAR proteins and reduced estradiol and progesterone secretion in bovine granulosa cells. However, the involvement of AMPK activation in steroid secretion in normal granulosa cells of some species is reported in previous studies that were stimulated by Aicar and insulin sensitizer drugs like metformin.…”
Section: Figurementioning
confidence: 99%
“…However, the involvement of AMPK activation in steroid secretion in normal granulosa cells of some species is reported in previous studies that were stimulated by Aicar and insulin sensitizer drugs like metformin. 15,59 Tosca et al showed that AMPK activation through Aicar could decrease the abundance of HSD3B, CYP11A1, and STAR proteins and reduced estradiol and progesterone secretion in bovine granulosa cells. 18 Obtained findings in the present study also showed that increased phosphorylation levels of AMPK through vitamin D3 treatment could decrease mRNA expression levels of aromatase, 3β-HSD, Cyp11a1, and StAR genes in granulosa cells of PCOS mice.…”
Section: Figurementioning
confidence: 99%